Working visit to universities and industries in Saudi Arabia - Helmi, Mohamed Isa (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) had a working visit to Saudi Arabia from Feb 28 until March 10, 2013 aimed at boosting its international research grant and strengthening ties with universities and industries in the country.